466 Transvenous Phrenic Nerve Stimulation for Central Sleep Apnea: A Systematic Review. (3rd May 2021) - Sagalow, Emily; Ananth, Ashwin; Fares, Elie; Fast, Zhanna
Abstract: Introduction: RespiCardia™ remedē® System, a transvenous phrenic nerve stimulator, is indicated to treat central sleep apnea (CSA) in certain patients. CSA involves disruption of the normal breathing pattern during sleep; CSA is associated with decreased patient quality of life and worsens cardiovascular outcomes. Existing therapies for CSA are often complicated by poor patient adherence to therapy and occasional adverse effects. The remedē® System uses electrical stimulation of the phrenic nerve to cause diaphragmatic contraction and attempts to restore normal breathing during sleep. Methods: Systematic review was conducted according to the Preferred Reporting of Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Databases were queried by two independent reviewers for English-language studies published between 2000 and 2020. The initial search screened for all occurrences of "remede" then was further refined to include studies evaluating use of the RespiCardia™ remedē® System as a treatment for CSA in multiple patients. Results: Two hundred twenty-seven articles were identified from initial search results. Fourteen articles were identified through screening of title and abstracts from initial results. Seven additional articles were identified through reference review. Full-text review of all the articles was then completed. All articles were published after 2010. Of the 21 articles, a total of 1621 patients underwent device implantation. We sought to summarize the available evidence regarding patient selection for implantation, immediate and delayed complications, adherence to therapy, and polysomnographic evidence of efficacy. Conclusion: The remedē® System has been demonstrated to improve sleep and respiratory parameters including AHI, CAI, arousal index, REM sleep, and ODI with few complications. This device proves to be a safe and effective treatment for moderate to severe CSA in adult patients, especially those with HF. Future studies examining long-term outcomes and delayed complications are needed. Support (if any):